'Inherent vice': marine insurance, slave ship rebellion and the law. (January 2016) - Rupprecht, Anita
Reparations activism has forced many large multinational insurance corporations to disclose their early profiteering from underwriting slavery and the slave trade. This paper further contributes to the reparative project of tracing slavery's occluded legacies by analysing aspects of the development of British, French and American marine insurance law in response to shipboard rebellion in the transatlantic slave trade, and the American 'domestic' maritime slave trade. It explores the ways in which marine insurance developed and adapted its ancient legal concepts – notably, the concept of 'inherent vice' – to the requirements of commodifying life for the purposes of modern slave trading. This history further illuminates the conceptual lineaments and practices that were involved in the slave trade's processes of dehumanisation but it also highlights the ways in which marine insurance lawyers, in the face of shipboard rebellion, were compelled to debate not only the humanity of the enslaved but their desire for freedom. In this context, the archive of marine insurance offers an unexpected route into the history of resistance to slavery.